If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3g + -5) = -2(46 + 3) Reorder the terms: 4(-5 + 3g) = -2(46 + 3) (-5 * 4 + 3g * 4) = -2(46 + 3) (-20 + 12g) = -2(46 + 3) Combine like terms: 46 + 3 = 49 -20 + 12g = -2(49) Multiply -2 * 49 -20 + 12g = -98 Solving -20 + 12g = -98 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 12g = -98 + 20 Combine like terms: -20 + 20 = 0 0 + 12g = -98 + 20 12g = -98 + 20 Combine like terms: -98 + 20 = -78 12g = -78 Divide each side by '12'. g = -6.5 Simplifying g = -6.5
| (x-10)(2x-10)=600 | | 4b+2b=66 | | 7•11/5 | | 10(319-a)+20a=5860 | | 5x+9=17x-7 | | 29=9 | | 138=6s^2 | | a=4x+30 | | y=100+.8x | | ln(2-x)+1=0 | | -4x+3(6x+14)=140 | | -7y+5(y+5)=23 | | 1=2sinx-1 | | -7x+6(2x+3)=58 | | 5b+2=2b+17 | | -7x+21(-x-18)=-108 | | a+2a=252 | | 10+6t=7t | | -2x+5(-5x+14)=-119 | | 4x-1(x+2)+6=2(3x+8) | | 2x^2-12x+32x=x^2 | | X-2y=100 | | -5(3t-5)+9t=4t-4 | | 9x+7=73-2x | | 5r+7= | | 6(3n+2)=6(8n+8)+9 | | 10+40+10x-15=18 | | 2.3x-15=45 | | 9x+15=126 | | 9+15=126 | | 2a-12+8a=3a+7+9 | | 5x/4=6.7 |